A Giant Right Heart Thrombus-in-Transit: The Challenge of Anticoagulation in Factor V Leiden Thrombophilia. (27th September 2018) - Chu, Andrew; Aung, Thu Thu; Arumugam, Minni Shreya; Danckers, Mauricio; Mitiek, Mohi; Leslie, Jonathan
Abstract : Factor V Leiden (FVL) is an autosomal dominant condition resulting in thrombophilia. Factor V normally acts as a cofactor for prothrombinase, helping cleave prothrombin to thrombin. A single point mutation in it disrupts factor V, making it unreceptive to protein C and increasing the risk of thrombosis. FVL mutation associated with right heart thrombus is a rare entity. Right heart thrombus or right heart thrombus-in-transit is associated with high mortality. We present a 51-year-old male with a past medical history of FVL homozygous mutation and recurrent blood clots, who has failed multiple different oral anticoagulants. He presented to the hospital with symptoms of shortness of breath and subsequently found to have a giant right heart thrombus. He was treated with surgical embolectomy. This case underscores the challenges faced by patients with FVL and recurrent blood clots.